Pre‐pregnancy BMI: Costs associated with maternal underweight and obesity in Queensland. (15th January 2013) - Watson, Melanie; Howell, Stuart; Johnston, Trisha; Callaway, Leonie; Khor, Sue‐Lynne; Cornes, Sue
Abstract : Background: The economic costs of maternal obesity and underweight have not been described. We aim to assess the effect of maternal underweight and obesity on hospital utilisation and hospital costs. Methods: Data from the Queensland Perinatal Data Collection and Queensland Hospital Admitted Patient Data Collection were analysed for 2008. The sample included 37, 912 Queensland resident mothers with a singleton pregnancy who gave birth in a public facility. Outcome measures were hospital length of stay (LOS) and hospital costs accrued during the birth admission and during pre‐ and postnatal admissions within 90 days of the birth admission. Results: There were 1, 581 (4.2%) underweight, 17, 175 (45.3%) normal weight, 10, 155 (26.8%) overweight and 9, 001 (23.7%) obese women. Maternal obesity was associated with significantly longer stays although effect sizes were modest (≤0.5 days) and specific to women who delivered vaginally. LOS was significantly higher among babies born to underweight mothers when compared to those born to normal weight women. Maternal obesity was associated with a total increase of 5 million in mothers' hospital costs when compared to those amongst normal weight women; the corresponding figure for underweight mothers was 385, 734. The total hospital costs for babies born to underweight women were 1.6 million higher than those born to mothers in the normal weight category. Maternal obesity was not associated with an increase in babies' hospital costs. Conclusions: Maternal obesity contributed to an increase in mothers' hospital LOS and hospitalisation costs. Maternal underweight contributed to an increase in babies' hospital costs.